Middle Eastern monarchies: ingroup identity and foreign policy making - Sunik, Anna (Routledge studies in Middle Eastern politics, 2021)
Introduction : explaining the dynamics of "monarchic peace" -- Moving beyond democratic exceptionalism : the peace among similar political systems -- Middle East monarchies from the "Arab Cold War" to the "Arab Spring" -- When monarchies collide : case studies of "near misses" of monarchic war -- From monarchy to republic, from peace to war? : "quasi-experiments" of collapsed monarchic couples -- The limits of SPSP : deviant cases? -- Conclusion : towards a peace among similar political systems.